At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
We can multiply the first equation by -1 then add it to the 2nd equation:
7x - 6y = -16
-7x + 6y = 16
-7x + 6y = 16
8x - 6y = -20
x + 0 = -20
x = -4
So our x-value is -20, we can plug this into any of the two equations to get the y-value:
8x - 6y = -20
8(-4) - 6y = -20
-32 - 6y = -20
Add 32 to both sides:
-6y = 12
y = -2
So our final answer is (-4, -2).
7x - 6y = -16
-7x + 6y = 16
-7x + 6y = 16
8x - 6y = -20
x + 0 = -20
x = -4
So our x-value is -20, we can plug this into any of the two equations to get the y-value:
8x - 6y = -20
8(-4) - 6y = -20
-32 - 6y = -20
Add 32 to both sides:
-6y = 12
y = -2
So our final answer is (-4, -2).
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.